RETRACTED: PENGARUH PENGGUNAAN LKS BERBASIS INKUIRI TERBIMBING MATERI ELASTISITAS DAN HUKUM HOOKE TERHADAP HASIL BELAJAR SISWA - Kartika Nurcahyati; I Wayan Distrik; Ismu Wahyudi (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2019)
This article has been retracted as a result of multiple publications from the article by the relevant author. Similar article can be found at Pascal (Journal of Physics and Science Learning) Vol. 2, No. 2 with url https://jurnal.uisu.ac.id/index.php/PASCAL/article/view/936